Protection of cyanidin-3-O-glucoside against acrylamide- and glycidamide-induced reproductive toxicity in leydig cells. (September 2018) - Sun, Jianxia; Li, Mingwei; Zou, Feiyan; Bai, Shun; Jiang, Xinwei; Tian, Lingmin; Ou, Shiyi; Jiao, Rui; Bai, Weibin
Abstract: Acrylamide (AA) occurs in many cooked carbohydrate-rich foods and has caused widespread concern as a possible carcinogen. Glycidamide (GA) is the ultimate genotoxic metabolite of AA. The present study was to investigate the protective effect of Cyanidin-3- O -glucoside (C3G) against AA- and GA-induced reproductive toxicity in R2C Leydig cells. The results demonstrated that C3G inhibited AA- and GA-induced cytotoxicity and mitochondria-mediated cell apoptosis, the effective doses of C3G were ranging from 10 to 50 μM. Besides, AA (1.925 mM) and GA (0.872 mM) exposure increased ROS level and decreased mitochondrial membrane potential, which led to a decrease in progesterone production, while C3G ranging from 10 to 50 μM reduced ROS immediately, and increased progesterone production after 24 h treatment. Furthermore, C3G up-regulated expression of Bcl-2 protein and down-regulated pro-apoptotic protein Bax and cleaved Caspase-3 after 24 h treatment in 1.925 mM AA- and 0.872 mM GA-treated R2C cells. Moreover, C3G intervention increased the protein expression of steroidogenic acute regulatory (StAR). It was concluded that C3G is effective in reducing AA- and GA-induced reproductive toxicity via inhibition of ROS generation, mitochondrial membrane depolarization and apoptosis, as well as activating steroidogenic enzymes.